Letter (copy) : International Brigade Association - Feather, Victor
035-0123-001 Organisation VF/RC/166. 30th September, 1942. Mr. G. West, Stepney Trades Council, 245-9, Whitechapel Road, E.1. Dear Mr. West, INTERNATIONAL BRIGADE ASSOCIATION. Thanks for your letter intimating that you have been appointed as Secretary of the Stepney Trades Council in succession to Mr. Silverman. I hope you have a successful term of office, and any advice or guidance which you may require will be very gladly given; please do not hesitate to write for any information you may require. In connection with your query on the above matter, arising from the desire of your Council to send a small donation, I should say that, whilst it is not a proscribed organisation, any co-operation with it or assistance in any way cannot be advised. The International Brigade Association has been and is consistently in support of Communist Party policy, and some of its most prominent officers are members of the Communist Party. There is an evergrowing list of appeals sponsored by bodies unconnected with our Movement, and it is felt that funds of sections of the Movement can best be safeguarded and grants most usefully employed by appeals directly sponsored or endorsed by the Movement itself. Yours sincerely, Acting Secretary, Trades Councils' Joint Consultative Committee. 292/946/35/123